Genetic polymorphisms in collagen-related genes are associated with pelvic organ prolapse. Issue 2 (February 2020) - Li, Lei; Sun, Zhijing; Chen, Juan; Zhang, Ye; Shi, Honghui; Zhu, Lan
Abstract: Objective: Pelvic organ prolapse (POP) is a common health issue that has a profound negative influence on women's quality of life. Genetic susceptibility to POP has been increasingly investigated. In this study, we assessed the single-nucleotide polymorphisms (SNPs) of six collagen-related genes ( COL14A1, COL5A1, COL4A2, COL3A1, COL1A1, and COL18A1 ) and the genetic association with POP in Chinese women. Methods: We performed a candidate gene association study of case women (n = 48) with stage III and IV prolapse and control women (n = 48) without prolapse. A target region sequencing approach was used to identify the SNPs in collagen-related genes. The association between SNPs and POP was examined by Fisher exact tests for unadjusted model and logistic regression analysis adjusted for delivery and pregnancy. Results: There was a significant association between COL14A1 SNPs (rs4870723, rs2305600, and rs2305598; P = 0.013, 0.019, and 0.028, respectively), a COL5A1 SNP (rs3827852; P = 0.016), and COL4A2 SNPs (rs76425569, rs388222, and rs2281968; P = 0.049 for the three, and rs445348, P = 0.040) and POP, respectively. Although there was no significant association between the COL3A1 SNP and POP, there was a trend toward significance for COL14A1 SNP (rs2305603), COL4A2 SNP (rs74941798), two COL1A1 SNPs (rs2586488 and rs2249492) and three COL18A1 SNPs (rs1050351, rs56335679, and rs55690336), and POP. Conclusion: We are the first to evaluate the relationship between COL14A1, COL5A1, and COL4A2 polymorphisms and POP, besides COL3A1, COL1A1, and COL18A1, which have been reported previously. We found several candidate SNPs that were significantly associated with prolapse in Chinese women. Our results provide new evidence for further investigation of the involvement of these potential genes in the etiology of POP. Abstract : Supplemental Digital Content is available in the text